2019
DOI: 10.1111/eva.12832
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of selection for bonamiosis resistance in European flat oyster (Ostrea edulis): New genomic tools for breeding programs and management of natural resources

Abstract: The European flat oyster (Ostrea edulis) is a highly appreciated mollusk with an important aquaculture production throughout the 20th century, in addition to playing an important role on coastal ecosystems. Overexploitation of natural beds, habitat degradation, introduction of non‐native species, and epidemic outbreaks have severely affected this important resource, particularly, the protozoan parasite Bonamia ostreae, which is the main concern affecting its production and conservation. In order to identify ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
63
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(81 citation statements)
references
References 70 publications
(135 reference statements)
15
63
3
Order By: Relevance
“…The low global genetic differentiation of flat oyster in the Adriatic Sea (F ST = 0.0082) was similar to levels previously documented using polymorphic SNPs (F ST = 0.0061; Vera et al, 2019) and 16 microsatellite loci (F ST = 0.0079; Vera et al, 2016) on a broad sample collected from the Atlantic area. When populations from the Mediterranean and Atlantic regions were analyzed together using five microsatellite loci, interpopulation differentiation was found to be slightly increased (F ST = 0.019) and followed the isolation by distance pattern, separating populations according to geographic origin (Launey et al, 2002).…”
Section: Discussionsupporting
confidence: 86%
“…The low global genetic differentiation of flat oyster in the Adriatic Sea (F ST = 0.0082) was similar to levels previously documented using polymorphic SNPs (F ST = 0.0061; Vera et al, 2019) and 16 microsatellite loci (F ST = 0.0079; Vera et al, 2016) on a broad sample collected from the Atlantic area. When populations from the Mediterranean and Atlantic regions were analyzed together using five microsatellite loci, interpopulation differentiation was found to be slightly increased (F ST = 0.019) and followed the isolation by distance pattern, separating populations according to geographic origin (Launey et al, 2002).…”
Section: Discussionsupporting
confidence: 86%
“…southeast Ireland and Wales) using a classical RADseq technique (Etter et al, 2011). Genetic diversity observed for C. edule in our study was similar to that reported for the sister species C. glaucum (He: 0.078 -0.137; Sromek et al, 2019); however, both cockle species showed lower genetic diversity at genomic scale than other bivalves such as Placopecten magellanicus (He = 0.271 ± 0.133, Van Wyngaarden et al, 2017), Crassostrea virginica (He ~ 0.300; Bernatchez et al, 2019), Ostrea edulis (He ~ 0.300; Vera et al, 2019) and Crassostrea gigas (He ~ 0.300; Gutierrez et al, 2017), suggesting the lower genetic diversity to be a particular feature of the genus Cerastoderma, although we cannot discard that the different methodologies applied for SNP genotyping in those studies might explain this observation.…”
Section: Genetic Diversitysupporting
confidence: 89%
“…Moreover, genetic diversity existing in the wild is important for commercial species, such as C. edule, to support breeding programs for selecting high-value seed for intensive production in particular areas (Lallias et al, 2010;do Prado et al, 2018;Petereit et al, 2018;Vera et al, 2019). Genetic diversity was similar across all cockle beds studied in the Northeast Atlantic, especially when no polymorphic filtering criterion was applied (MAF; He range: 0.077 -0.086).…”
Section: Genetic Diversitymentioning
confidence: 99%
“…Comparisons of gene expression profiles in Bonamia-free and -infected oysters are producing suites of candidate resistance conferring genes (e.g. Ronza et al, 2018;Vera et al, 2019) for testing and screening resistance.…”
Section: Evidence For Tolerance or Resistance In Existing O Edulismentioning
confidence: 99%
“…Comparisons of gene expression profiles in Bonamia ‐free and ‐infected oysters are producing suites of candidate resistance conferring genes (e.g. Ronza et al, 2018; Vera et al, 2019) for testing and screening resistance. Proteomic approaches can also contribute to identify molecular markers of resistance to bonamiosis (de la Ballina, Villalba, & Cao, 2018).…”
Section: Characteristics Of B Ostreae and Bonamiosis And The Relevanmentioning
confidence: 99%